THE INFLUENCE of CHAIN STORY TECHNIQUE in SPEAKING SKILL - Aini, Nur; Hatip, Mochammad; Kamilah, Nur (FKIP UNISKA, 2024)
This study aims to determine the influence of using the chain story technique on speaking skills. This research design is pre experimental (static group comparison). The subjects of this study were eighth grade students of SMPN 02 Ledokombo consisting of 44 students from 2 classes. Data were obtained through speaking tests. The results showed that there was a change between the experimental class and the control class, seen based on the average value of the experimental class of 59.77 superior to the control class of 50.91. After being tested using the independent t-test, it shows a significance of 0.043 that the value is less than 0.05 in accordance with the predetermined significance level. These results indicate that the null hypothesis is rejected and the alternative hypothesis is accepted. So, it can be concluded that the chain story technique is very effective to be applied to speaking skills.